Analyzing the measurements of gonial angle by panoramic radiographs for forensic estimation in Iraqi population (Mustansiria Dental Journal, 2018)
Aim: this study aimed to measure the size of gonial angle on digital panoramic radiography and correlate these measurements with age, gender, and dentate status and this determination of sex and age is necessary in forensic practice and medicolegal purposes, therefore the usefulness of gonial angle measurements on digital panoramic images as indicators for sex and age in Iraqi population sample.Materials and Methods: this study conducted on 40 Iraqi subjects (21 male and 19 female) aged from (20-80) years. Subjects were divided in to 2 study groups• Dentulous study group ( 20 subjects )• Edentulous study group ( 20 subjects )Using digital panoramic image, the gonial angle was measured on both right and left sides for 2 study groupsResults:• According to the age: in both dentulous and edentulous study groups, there was significant difference in mean gonial angle (GA) between 2 age groups (younger and older age groups) , the mean GA was significantly higher in the older age group , P value < 0.001• According to the gender: in dentulous study group there was non-significant difference in mean GA between males and females , P value = 0.76 while in edentulous study group , the mean GA was significantly higher in females , P value = 0.01• According to the dentate status: the edentulous study group statistically significant higher mean GA compared to dentulous study group, P value < 0.001Conclusions: gonial angle does show changes with dentition status (edentulism) , therefore dentist role in qualitative and quantitative assessment of mandibular gonial angle by using digital panoramic radiography has become an essential aid for human identification in forensic dentistry.